Dampak Putusan MK Nomor 80/PUU-XX/2022 terhadap Kewenangan Komisi Pemilihan Umum dalam Penataan Daerah Pemilihan - Aryo Wasisto (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2023)
The Constitutional Court Decision Number 80/PUU-XX/2022 in the case of reviewing Law Number 7 of 2017 on General Elections against the 1945 Constitution of the Republic of Indonesia, ordered the General Election Commission (KPU) to arrange electoral districts at all levels. The decision stated that the list of electoral districts in the Election Law was unconstitutional. The KPU followed up on this decision by drafting a KPU Regulation but did not revise the composition of the electoral districts of the DPR and Provincial DPRD. Using a political-legal approach, this study analyzes the KPU’s follow-up options and their potential implication. This study also explains the implication of strategic choices that the KPU may take, such as the status quo, moderate actions, and progressive actions. The results of this study conclude that the choice of the status quo fulfills the formal aspect of the decision. The basis for the KPU’s choice was the absence of an order to revise the electoral districts. From a social perspective, changing electoral districts in the midst of an election process will lead to distortions of democracy and the relationship between constituents and members of parliament. This choice has an institutional implication and raises questions about the independence of the KPU in electoral arrangements. It is considered that the KPU did not take advantage of the momentum to arrange electoral districts in a professional manner, which has been a problem since the 2009 election.AbstrakPutusan Mahkamah Konstitusi (MK) Nomor 80/PUU-XX/2022 dalam perkara pengujian Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum (Undang-Undang Pemilu) terhadap Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 memerintahkan Komisi Pemilihan Umum (KPU) untuk menata daerah pemilihan (dapil) di seluruh tingkatan. Putusan tersebut juga menyatakan daftar dapil dalam Undang-Undang Pemilu inkonstitusional. Tujuan artikel ini menjelaskan dinamika kewenangan pengaturan dapil, menganalisis dampak Putusan MK, dan menganalisis pilihan tindak lanjutnya oleh KPU. Dari hasil penelitian ini diketahui bahwa KPU telah mendapatkan kembali wewenang mengatur seluruh daerah pemilihan pasca-Putusan MK. KPU menindaklanjuti putusan tersebut dengan menerbitkan Peraturan KPU, tetapi tidak merevisi susunan dapil DPR dan DPRD Provinsi. Dari perspektif sosial, perubahan dapil di tengah tahapan pemilu akan menimbulkan distorsi demokrasi antara konstituen dan anggota parlemen. Keadaan ini menimbulkan pertanyaan tentang independensi KPU dalam tata kelola dapil. KPU dianggap tidak memanfaatkan momentum untuk mengatur dapil secara profesional. Hal ini telah menjadi masalah sejak Pemilu 2009.